Below‐ground determinants and ecological implications of shrub species' degree of isohydry in subtropical pine plantations. Issue 6 (12th May 2020) - Jiang, Peipei; Meinzer, Frederick C.; Wang, Huimin; Kou, Liang; Dai, Xiaoqin; Fu, Xiaoli
Summary: The degree of plant iso/anisohydry is a popular framework for characterising species‐specific drought responses. However, we know little about associations between below‐ground and above‐ground hydraulic traits as well as the broader ecological implications of this framework. For 24 understory shrub species in seasonally dry subtropical coniferous plantations, we investigated contributions of the degree of isohydry to species' resource economy strategies, abundance, and importance value, and quantified the hydraulic conductance ( K h ) of above‐ground and below‐ground organs, magnitude of deep water acquisition (WAdeep ), shallow absorptive root traits (diameter, specific root length, tissue density), and resource‐use efficiencies ( A max, maximum photosynthesis rate; PNUE, photosynthetic nitrogen‐use efficiency). The extreme isohydric understory species had lower wood density (a proxy for higher growth rates) because their higher WAdeep and whole‐plant K h allowed higher A max and PNUE, and thus did not necessarily show lower abundance and importance values. Although species' K h was coordinated with their water foraging capacity in shallow soil, the more acquisitive deep roots were more crucial than shallow roots in shaping species' extreme isohydric behaviour. Our results provide new insights into the mechanisms through which below‐ground hydraulic traits, especially those of deep roots, determine species' degree of isohydry and economic strategies.